Hydrodynamics of rowing propulsion - Grift, E. J.; Tummers, M. J.; Westerweel, J. (Journal of Fluid Mechanics, 2021)
This paper presents the results of the time resolved flow field measurements around arealistic rowing oar blade that moves along a realistic path through water. To the authors`knowledge no prior account of this complex flow field has beengiven. Simultaneouslywith the flow field measurements, the hydrodynamic forces acting on the blade weremeasured. These combined measurements allowus to identify the relevant flow physicsthatgoverns rowing propulsion, and subsequently use this information to adjust the oarblade configuration to improve rowing propulsion. Analysis of the instationary flow fieldaround the oar blade during the drive phase indicated how the initial formation, andsubsequent development, ofleading-edgeandtrailing-edge vortices are related to thegeneration of instationary lift and drag forces, and how these forces contribute to rowingpropulsion. It is shown that the observed individual flow mechanisms are similar tothe flow mechanisms observed in bird flight, but that the overall propulsive mechanismfor rowing propulsion is fundamentally different. To quantify the rowing propulsionefficiency, we introduced the energetic efficiency EtaE and the impulse efficiency EtaJ, wherethe latter can be interpreted as the alignment of the generated impulse with the propulsivedirection. It is found that in the conventional oar blade configuration, the generated impulseis not aligned with the propulsive direction, indicating that the propulsion is suboptimal.By adjusting the angle at which the blade is attached to the oar, the generation ofleading-andtrailing-edge vortices is altered such that the generated impulse better aligns with thepropulsive direction, thus increasing the efficiency.